Opolnomočenje civilnodružbenih organizacij v Sloveniji - Rakar, Tatjana (Teorija in praksa, 2016)
On the basis of civil society research in Slovenia, the authors analyse the empowerment of civil society organisations as carriers of civil dialogue. The analysis shows that in Slovenia civil society organisations have general support from the government and that they are invited to participate in the preparation of policies, yet their actual role and contribution to social welfare and cohesion is disregarded. Slovenia is still in the process forming the structure for the actual implementation of civil dialogue and shows a clear discrepancy between the activity (and scope) of civil society and its influence within society and towards the state. The analysis shows that in Slovenia the relationship between civil society organisations and the state can be placed in the model of "separate autonomy", characterised by low government financing and the moderate autonomy of civil society organisations as well as a low level of communication and contacts between civil society organisations and the state. Hence, the conclusion is that the level of the civil society sector's empowerment in Slovenia is relatively low.
Keywords: Civil society; Civilna družba; Connection; opolnomočenje; Organizacije; Organizations; Povezanost; Slovenia; Slovenija